Sanksi Pidana terhadap Pelaku Penista Agama Studi Kasus Putusan Pengadilan Negeri Pandeglang Nomor : 28/Pid.Sus/2018/PN Pdl - Amirulloh Ahdad; Ridwan Ridwan; Reine Rofiana (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
The polemic on the issue of blasphemy or better known as blasphemy has again become a discussion on the topic of this problem, especially in Indonesia because of the massive flow of information and freedom of opinion. Like a Pandeglang resident, especially a resident of Gadog Village who was entangled in a blasphemy case. Based on his actions, the articles charged against Arnold are: Article 45A paragraph (2) of ITE Law No. 19/2016. This research is normative juridical research, which is research conducted or aimed only at written regulations or legal materials consisting of secondary materials including Judges' Decisions, laws and regulations, books, journals, and other literature and supported by data obtained through interviews. This research resulted in the conclusion that the judge's legal considerations in this decision lacked a sense of justice, especially for the defendant. The panel of judges only considers witnesses and experts who incriminate the defendant and does not consider the defendant's testimony. The decision of the Pandeglang District Court Judge was corrected by the Banten High Court Judges on one of the grounds that the length of the sentence (strafmaat) imposed on the defendant did not pay attention to the purpose of punishment and the rules of justice for all parties, not just one of the parties. The Judex facti/High Court in its judgment hesitated to say that the screenshot was not maintained integrity and the Public Prosecution did not conduct digital forensics on the Facebook status on which the charges were based, but the Judge still found the Defendant guilty of his actions.